Protein phosphatase PP2C in the flagellum of Leishmania major: cloning and characterization. (6th November 2017) - Escalona-Montaño, A. R.; Pérez-Montfort, R.; Cabrera, N.; Mondragón-Flores, R.; Vélez-Ramírez, D. E.; Gómez-Sandoval, J. N.; Gutiérrez-Kobeh, L.; Becker, I.; Aguirre-García, M. M.
Abstract: The main goal of this work consisted in cloning, purifying and characterizing a protein phosphatase 2C (PP2C) from promastigotes of Leishmania major . The gene was cloned and amplified by PCR using specific oligonucleotides and the recombinant protein was purified by affinity chromatography. The peak with maximal protein concentration was analysed by sodium dodecyl sulphate-polyacrylamide gel electrophoresis and revealed a protein of 44·9 kDa with PP2C activity. This activity was dependent on divalent cations (Mg +2 and Mn +2 ) and was optimal at pH of 8·5, using phosphothreonine as the substrate. Sanguinarine inhibited the activity of the recombinant Lm PP2C, while protein tyrosine phosphatase inhibitors had no effect. The recombinant Lm PP2C was used to generate polyclonal antibodies. These antibodies recognized a protein of 44·9 kDa in different Leishmania species; the Lm PP2C was localized in the flagellar pocket and the flagellum of promastigotes.